Influence of team pressing on match performance in highest-level soccer; preliminary report - Modric, T.; Gabrilo, G.; Sekulic, D. (Kinesiologia Slovenica, 2023)
Considering lack of studies which investigated pressing behaviour in soccer, this study aimed to preliminary examine the influence of successful team pressing on team running performance (TRP) and team technical-tactical performance (TTP). All data were obtained from UEFA Champions League (UCL) matches (n=20) using optical system InStat Fitness. The TRP variables included total distance covered, low-intensity running (<4 m/s), running (4-5.5 m/s), high speed running (5.5-7 m/s) and sprinting (>7 m/s). The TTP variables included total actions shots on target, passes, key passes, crosses, dribbles, final third entries and penalty area entries. Results from linear mixed model indicated that (i) TRP was similar irrespective to number of successful pressings (t=-0.13 to 0.67, all p>0.05, all trivial to small effects sizes), (ii) TTP tend to increase when higher rate of successful team pressings was utilized (t=2.33 to 5.18, all p<0.05, all large effects sizes). These results show significant influence of team pressing on TTP and no influence of team pressing on TRP, suggesting that cooperative and well-organised interaction between players is more important factor of team pressing than pure physical performance. This study may help soccer coaches to better understand physical and technical-tactical profiles of teams that utilize pressing style of play.